PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK NUMBERED HEADS TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 HILIRAN GUMANTI KABUPATEN SOLOK - Yarni, Fitra; Anggraini, Villia; Melisa, Melisa (STKIP PGRI Sumbar, 2014)
ABSTRACTThis research was conducted due to the studentsâ less confidence to express ideas, inability to work in a group and low understanding on mathematics concepts. The aim of the research was to reveal whether the mathematics conceptual understanding of the students taught by Numbered Heads technique cooperative learning model was better than that of students taught by using conventional learning. This was an experimental research which used random toward the subject design. The population of the research was the students in class VIII of SMPN 2 Hiliran Gumanti. By using random sampling technique. The instrument of the research was a post-test. Based on the result of data analysis, it was found that the value of tcalculatedÂ was bigger than ttable. This result signified that the mathematics conceptual understanding of the students taught by using Numbered Heads technique cooperative learning model was better than that of students taught by using conventional learning.